PROBLEMS OF THE MAIN ACTIVITIES OF PHARMACEUTICAL WORKERS TO PRESERVE THE HEALTH OF HIV-INFECTED PATIENTS - Филимонов, Сергей Николаевич; Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич (Medicine in Kuzbass, 2023)
Identification of the professional capabilities of pharmaceutical specialists in the field of personalized and specialized pharmaceutical care for HIV-infected patients is possible only through the formation of conditions for sustainable opportunities of professional competencies that form the professional requirements necessary for the prevention and treatment of HIV-infected patients. The purpose of the study is a methodological substantiation of the professional knowledge of the pharmaceutical profile from the standpoint of the implementation of the main activities of pharmaceutical workers to preserve the health of HIV-infected patients. Material and methods. The substantiation of the professional knowledge of the pharmaceutical profile from the standpoint of the implementation of the main activities of pharmaceutical workers to preserve the health of HIV-infected patients was carried out using the method of expert assessments and their programmatic statistical processing in the Statistica 10 program. Results. The necessity of formation of special professional knowledge among pharmaceutical workers in the field of prevention and treatment of HIV-infected patients, in particular, the ability and readiness of pharmaceutical workers for personalized pharmaceutical counseling of HIV-infected patients, information support of medical workers and activities in the field of pharmaceutical education is substantiated. It is proposed to include in the professional standard «Clinical pharmacist» the main labor functions in the field of information and consulting support for the rational choice of pharmacotherapy, personification of pharmaceutical services for HIV-infected patients, conducting prophylactically oriented sanitary and educational activities and promoting a healthy lifestyle. The results of the expert assessment made it possible to determine the importance of the knowledge of pharmaceutical workers in the context of preventive and anti-epidemic work with HIV-infected patients, confirmed the high level of expert expectations from these specialists in terms of the implementation of their work functions and allowed to form the main directions of socio-personal characteristics for the much-needed position of "Clinical pharmacist" in the center for the prevention and control of AIDS and hospitals of infectious diseases hospitals in the region. Conclusion. The main professional areas of activity of pharmaceutical workers in the field of prevention and treatment of HIV-infected patients are identified, amendments to a number of regulatory documents are recommended, approximate necessary knowledge of specialists (Clinical pharmacist) for carrying out activities in the field of health protection of the population of the region is proposed.